Evaluasi Program Mahasiswa Wirausaha (PMW) di Universitas Negeri Jakarta - Nuwrile Ard Khiyari; Wahyu Sri Ambar Arum; Siti Zulaikha (Universitas Negeri Jakarta, 2017)
This research aims to give a description and information about Entrepreneur Student Program (PMW) that has been held at Jakarta State University. This evaluation research uses Context, Input, Process and Product (CIPP) model with evaluative approach and descriptive method. Data were collected through observations, interviews, questionnaire, documentation study that have been done in Jakarta State University. The result of research shows Entrepreneur Student Program has been well done and met the evaluation criteria; 1) evaluation result in program background, goal and need analysis has met the evaluation criteria and shows good in category but legal basis of the program management team should be made, 2) evaluation result in program human resources, objective and infrastructure of program has met the evaluation criteria but clear organizational structure should be made and human resources who are committed and competent in program implementation, 3) evaluation result in program preparation, provision, business run, monitoring and evaluation has met the evaluation criteria but the program management team need to monitor the performance of mentor and monitoring and evaluation team so that goal of monitoring and evaluation be achieved with good implementation, 4) evaluation result in program result and report has met the evaluation criteria but concrete efforts should be made to encourage the formation of organizations that specifically manages entrepreneurship program.